Gheorghe Eşanu - faithful fiancé of folk song (April 25, 1927 – March 19, 1996) (Confluenţe Bibliologice, 2026)
The article is about the life and work of Gheorghe Esanu, popular music singer. His repertoire was vast, interpreting successfully popular songs, ballads as well as songs of Moldovan composers. He scored a separate chapter in the history of national musical culture.
Keywords: Eşanu Gheorghe (1927-1996); folk music